Resistance in an Amazonian community : Huaorani organizing against the global economy - Ziegler-Otero, Lawrence (Berghahn Books, 2004)
Like many other indigenous groups, the Huaorani of eastern Ecuador are facing many challenges as they attempt to confront the globalization of capitalism in the 21st century. In 1991, they formed a political organization as a direct response to the growing threat to Huaorani territory posed by oil exploitation, colonization, and other pressures. The author explores the structures and practices of the organization, as well as the contradictions created by the imposition of an alien and hierarchical organizational form on a traditionally egalitarian society. This study has broad implications for those who work toward "cultural survival" or try to "save the rainforest."--